Tracheobronchial Injury caused by Blunt Trauma: Case Report and Review of Literature - Vandana Pandey; Dharam S Meena; Swati Choraria; Sushil Guria (Journal of Clinical and Diagnostic Research, 2016)
Tracheobronchial injuries are rare cases requiring skillful airway management. We report a challenging case of tracheobronchial injury in a young adult who was run over by a tractor and was referred to us from a peripheral hospital with endotracheal tube in situ. He was severely hypoxaemic on initial presentation. Diagnostic work up showed high suspicion for right bronchial transection along with left lung upper lobe contusion. Due to deteriorating clinical condition of the patient and despite immediate unavailability of fibreoptic bronchoscope, patient was immediately taken up for right posterolateral thoracotomy and double lumen tube was inserted. The position of the tube was confirmed clinically. As soon as the fibreoptic bronchoscope arrived, it was again used to confirm the position of double lumen tube. Patient’s clinical condition improved after repair of the injured right bronchus and he was later extubated the next day.